MANAJEMEN PEMBELAJARAN MENGENAL BENTUK GEOMETRI BERBASIS SENTRA BALOK DALAM MENINGKATKAN BERPIKIR KREATIF PESERTA DIDIK. - Komalasari, Dewi (PT. Solusi Komunikasi Terapan, 2023)
Developing creativity in early childhood is one of the educational problems that challenges educators and kindergarten managers. The teachers try to increase students’ creativity in recognizing geometric shapes through playing in the block center. This research uses a qualitative approach with descriptive methods. Data collection techniques are through observation and documentation, while data collection tools use interview and observation guidelines. Based on the results of research conducted regarding learning to recognize geometric shapes based on beam centers which was carried out in two kindergartens guided and supervised by teachers who have good competence, it can improve students’ creative thinking abilities. Students can develop their imagination, show exploratory activities, create works that look like real shapes using various materials, have great curiosity and have high perseverance when taking part in learning at the block center and understand geometric shapes and can apply them to recognize geometric shapes in everyday life